Perlunya dasar kategori pengajar di era digital - Hayati, Fatihah Nurul (Fakultas Sastra Universitas Negeri Malang, 2022)
In the era of now the community already familiar with the phenomenon digital. The more digital thrived without us knowing. So that all human activity is very convenient. Modern technology has become important things that can be used as the study. As the challenge of education and the abreast of developments moral and keep in the community. The digital era, need the required teachers and parents who able to follow, time progress to play various roles as a bringer of change networkers, digital learning consultant; humanity and having a high moral, social and sensitivity and less rational and honest, so that it can work well in a dynamic educational environment. To this article covered some new reorientation learning that ended up at re orientation on the new role parents and teacher, as agent of change, renewal knowledge and a consultant learning.